Impact of sleep disorders on the quality of life of nursing professional (Research, Society and Development, 2021)
The objective of this study was to analyze the impacts caused by sleep disorders on the quality of life of nursing professionals. To this end, a descriptive, quantitative research was carried out with 40 nursing professionals working in intensive care units in a public hospital in Teresina-PI, from February to April 2021. The questionnaires used were the Pittsburgh Sleep Quality Index and The World Health Organization Quality Of Life-Bref, via google forms. The collected data were stored in Microsoft Excel 2010 spreadsheets and analyzed with the Statistical Package of Social Science version 20.0. As a result, the components of the sleep questionnaire most affected were: subjective quality, latency, duration and dysfunction during the day. Poor sleep quality was observed in 95% of the participants, with insomnia being presented in 13%. As for the quality of life questionnaire, 50% rated it as good and 40% were dissatisfied with their health. The scores for each domain were transformed into a scale of 0-100; higher averages suggested better quality of life. The most compromised domain was the environment (related to the domestic environment, financial resources, leisure and the environment). The most affected facets were: sleep and rest, positive feelings, sexual activity, recreation and leisure. Thus, it was found that a large part of the sample suffers or has already suffered from sleep disorders. Thus, sleep quality is a factor that affects quality of life.